PENGARUH KONSERVATISME AUDITOR TERHADAP MANAJEMEN LABA DAN OPINI GOING CONCERN - Elsa Hidayati Fajriyah; Sudarno Sudarno (Diponegoro Journal of Accounting, 2020)
This research purpose is to analyze the effect of auditor conservatism (the audit firm size) on earnings management (discretionary accrual absolute) and going concern opinion. Some control variables that used in this research are tobin’s q, size, leverage, return on assets, market-to-book value, age, sales growth, dan cash flow from operation. This research uses quantitative method by using multiple linear regression analysis and logistic regression analysis. The population in this research is all minning sectors firm listed in the Indonesia Stock Exchange from 2014 - 2018. The sample is selected using purposive sampling method  and outlier test, and acquired 130 samples. The result showed that the auditor conservatism effect significantly on tax aggressiveness. Meanwhile, the auditor conservatism does not significantly influence on the relationship between earnings management and going concern opinion.